CLINICAL ASPECTS OF THYROTOXICOSIS SYNDROME. MODERN TREATMENT APPROACHES - A.B. Akhmedova (Western European Studies, 2024)
The thyroid gland is a small endocrine organ located in the neck, closely adjacent to the trachea and surrounded by large vessels. It has an active blood supply, several times more active than that of the heart muscle. This organ produces hormones responsible for metabolism and other biological processes and regulates the vital activity of the entire body.
Keywords: pituitary gland; thyretoxicosis; hyperthyroidism